Research on the restorative effects and perception of privacy driven activities in Chinese classical gardens—Case studies of three Suzhou gardens - Hanxin Liu; Hanxin Liu; Guoshu Bin; Guoshu Bin; Xiao Wang; Xiao Wang; Jia Luo; Minyi Liu (Frontiers in Public Health)
The need for privacy, recognized as a fundamental psychological requirement, has garnered increasing attention as researchers explore the restorative effects of privacy driven activities (PDA). This study employs quantitative experiments and analyses to assess the restorative benefits of PDA within three classical Chinese gardens, demonstrating their superiority over conventional leisure activities in promoting emotional recovery, reducing stress, and restoring attention. The experiment quantifies the restorative effects of PDA versus standard leisure activities using a classic restorative scale and physiological indicators reflecting emotional relief. Regression analyses then identify five key factors influencing the occurrence of PDA, derived from preferred locations and behavioral tendencies observed in the three gardens. Further analyses reveal significant differences in the impacts of these five environmental feature dimensions on the evaluation indicators of “preference for privacy-oriented activities” and “restorative effects”. Among these dimensions, “spatial scale and accessibility” has the greatest impact on the “preference for privacy-oriented environments”, while “spatial atmosphere” and “activity facilities” have the most significant impact on “restorative effects”. The findings suggest that behavioral activities mediate the relationship between environmental factors and restorative effects, highlighting the potential of PDA as a mediating variable for a comprehensive investigation into the pathways and mechanisms influencing restorative environments in research and design.